2008
DOI: 10.1001/jama.300.11.1317
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Adults With Bicuspid Aortic Valves

Abstract: Context Bicuspid aortic valve is the most common congenital cardiac anomaly in the adult population. Cardiac outcomes in a contemporary population of adults with bicuspid aortic valve have not been systematically determined. Objective To determine the frequency and predictors of cardiac outcomes in a large consecutive series of adults with bicuspid aortic valve. Design, Setting, and Participants Cohort study examining cardiac outcomes in 642 consecutive ambulatory adults (mean [SD] age, 35 [16] years; 68% male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
428
8
26

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 526 publications
(493 citation statements)
references
References 35 publications
15
428
8
26
Order By: Relevance
“…There have been conflicting reports regarding the association between BAV morphology and AVD [Fernandes et al, 2004;Tzemos et al, 2008]. Fernandes et al [2004] identified an association between RN BAV and AVD in a pediatric population, while Tzemos et al [2008] found no association in an adult population . Despite clear evidence that BAV is a heritable condition with a recurrence risk of approximately 8%, it remains unclear whether BAV morphology is also genetically determined and whether it predicts the development of AVD [Cripe et al, 2004;Fernandez et al, 2009;Hinton et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been conflicting reports regarding the association between BAV morphology and AVD [Fernandes et al, 2004;Tzemos et al, 2008]. Fernandes et al [2004] identified an association between RN BAV and AVD in a pediatric population, while Tzemos et al [2008] found no association in an adult population . Despite clear evidence that BAV is a heritable condition with a recurrence risk of approximately 8%, it remains unclear whether BAV morphology is also genetically determined and whether it predicts the development of AVD [Cripe et al, 2004;Fernandez et al, 2009;Hinton et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…AVD (stenosis and/or insufficiency) typically manifests later in life, affecting more than 2% of the population, and remains a significant surgical problem with approximately 100,000 valve replacement procedures performed each year in the US [Bonow et al, 2006;Nkomo et al, 2006;Otto, 2006;Rosamond et al, 2008;Lloyd-Jones et al, 2009]. The majority of AVD cases at any age have an underlying BAV, and longitudinal studies in young adults with BAV have shown that >20% ultimately develop AVD requiring intervention [Tzemos et al, 2008]. Two patterns of BAV morphology are commonly observed; $70% of cases have fusion of the right and left (RL) coronary cusps with the remainder consisting almost entirely of those with fusion of the right and non (RN) coronary cusps [Ward, 2000;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As BAV is one of the most common congenital cardiac abnormalities (11)(12)(13), the frequency of cardiac and vascular events associated with BAV might be greater than the combined cardiovascular morbidity of all other congenital heart diseases (2). High rates of cardiovascular adverse events in adults with BAV have been recently reported by two large-scale studies (14,15).…”
Section: Discussionmentioning
confidence: 94%
“…In a cohort of 310 patients with aortic valve IE (1), a BAV was identified in 16% of cases. In a study including 642 adults with BAV, IE occurred in 13 patients over 9 years of follow-up (15), while in another study, 4 out of 212 patients with BAV developed IE during a follow-up of 20 years (14). A recent multicentre study (1) demonstrated that of 148 patients with BAV, 4(2.7%) were diagnosed with IE.…”
Section: Discussionmentioning
confidence: 98%